PERFORMANCE EVALUATION OF STATE ADMINISTRATIVE APPARATUS IN CARRYING OUT DUTIES AND FUNCTIONS - Ade Risna Sari; Muhammad Syafri; Abdul Wahab Syakhrani (Prosiding Seminar Nasional Indonesia, 2024)
This study aims to evaluate the performance of state administrative officers in carrying out their duties and functions. The research method in this study is literature. The results show that individual competencies and skills play a key role in improving administrative performance. Apparatus who have adequate competence are able to carry out tasks more effectively and efficiently. High work motivation, which is driven by satisfaction and a positive work environment, also has a significant effect on improving performance. In addition, good technological infrastructure support has been shown to facilitate more efficient administrative tasks. This study also found that clear regulations and policies as well as effective leadership and management are critical in directing the performance of state administrative apparatus. Clear regulations and policies provide the necessary guidance, while strong leadership ensures smooth administrative processes. A positive work culture and ongoing training programs also contribute to improving performance. The conclusion of this study is that improving the performance of state administrative apparatus requires improvements in these various aspects, which will ultimately have a positive impact on the quality of public services and public welfare.